The BRICS+ Expansion, Global Trade Dynamics, and the Dedollarization Phenomenon - Lee, Brice Tseen Fu; Sims, Juan Pablo (Universitas Negeri Semarang, 2024)
This paper delves into the transformative role of the expanded BRICS bloc, referred to as BRICS+, in the evolving global economic landscape and its implications for dedollarization. The inclusion of nations such as Ethiopia, Saudi Arabia, Iran, Egypt, and the UAE diversifies the bloc's economic and geopolitical reach, extending its influence into new regions like Africa and the Middle East. The study underscores the potential of BRICS+ as a catalyst in the dedollarization narrative, driven by the desire for economic autonomy, geopolitical strategies, and hedging against U.S. dollar volatility. The analysis further explores the intricate relationship between the BRICS+ expansion, global trade dynamics, and dedollarization. The paper concludes by emphasizing the potential of the BRICS+ bloc to reshape global trade dynamics, influence trade policies, establish new trade routes, and foster regional connectivity, all while advancing the agenda of a more diversified and multipolar economic world order.